Integration of Information and Communications Technology into Teaching and Learning Activities: A Panacea for Nigeria’s Educational System for 21st Century Challenges - Job, Gabriel C. (West African Journal of Open and Flexible Learning, 2014)
This paper centred on the pervasiveness of information and communications technology (ICT) which has virtually taken over the way things are done in all spheres of human endeavour. It also reviewed the state of Nigerian education system from the perspective of low academic performances of the products of the various available institutions at different levels. It posited that in the absence of the identified challenges, effective integration of ICT into the teaching and learning activities will launch the nation into the apex of comity of nations that have attained the Millennium Development Goal in education.